Microelement composition investigation in peripheral blood and synovial fluid in osteoarthritis - Koktysh, Irina V.; Bashura, Anastasia M.; Koktysh, Vitaliy T.; Venskaya, Elena I.; Skarabahatava, Alexsandra S. (Journal of the Belarusian State University. Ecology, 2021)
It was determined the content of osteo-associated trace elements Ca, Zn, Cu, Fe in the peripheral blood and synovial fluid in patients with confirmed clinical and radiological signs of osteoarthritis. The determination of trace elements was carried out by the ICP AES method. There were found a statistically significant iron concentration decrease (p = 0,01) and an increase of calcium (0,003) and zinc (p = 0,01) in the peripheral blood in patients with osteoarthritis. At the same time, there were established in a study of the concentration of trace elements in the synovial fluid, a statistically significant increase of iron concentration (p = 0,01) and a decrease in the concentration of calcium (p = 0,01) and zinc (p = 0,02). A direct correlation was found between the degree of osteoarthritis and the concentration of calcium in peripheral blood (Rs = 0,66, p <0,001) in gonarthrosis. Statistically significant negative correlation was found between the iron concentration in the peripheral blood and the degree of osteoarthritis in gonarthrosis (Rs = -0,57, p <0,03). Analysis of the microelement composition of synovial fluid and peripheral blood can be used in the complex diagnosis of patients with deforming joint diseases.